PENAMBAHAN BESAR SUDUT INKLINASI INSOLE SEPATU KERJA MENURUNKAN KADAR GLUKOSA DARAH PUASA DAN HbA1c - kusuma, herdianty; Abdullah, Ahmad; Purwanto, Bambang; Suhartatik, Suhartatik (Jurnal NERS, 2016)
Introduction: Running downhill improved the expression of glucose transporter 1 (Glut 1) and fasting blood glucose in mouse. Eccentric contraction during running downhill found daily in activity such as down stairs and walking on tiptoe. Descend the stairs and walking on tiptoe are not easy to repeated, single, stable and universal, so that we purposed to replace it with additional insole in shoes for daily activity. The aim of this research was to investigate the effect of the additional shoe insole on fasting blood glucose and HbA1c. Method: This research using experimental pre and post test design with 12 subject female staff at Medical Faculty of Airlangga University for two weeks and the test was performed in three times. The blood was taken before and after using shoe insole. The shoe insole inclination designed into 50 and 100. All subjects used the shoe insole for a week. Result: The result research showed the fasting blood glucose and HbA1c on subject that use shoe insole lower than control group. The fasting blood glucose and HbA1c on subject that use shoe insole 100 has value p<0,05. Discussion: Application of shoe insole lead to reduce the fasting blood glucose and HbA1c.Keywords: shoe insole, fasting blood glucose, HbA1c, diabetes, eccentric.Â Â Â